Transforming your service: the right evidence at the right time and place. (9th September 2016) - Sutton, Anthea
Abstract: This virtual issue is published to coincide with the CILIP Health Libraries Group Conference 2016. The theme of the conference is Knowledge for Healthcare (KFH), the development framework for health care library and knowledge services (LKS), published by Health Education England. Transforming the service, and delivering the right evidence at the right time and place, is a key strategic focus of KFH. Therefore, this virtual issue draws on content published in Health Information and Libraries Journal (HILJ) in the last 2 years, which demonstrate initiatives in health care LKS in line with the transformation strands outlined in KFH. The virtual issue follows the same structure as a regular issue of HILJ, containing one review article, a series of original articles and our three regular features: Dissertations into Practice, Teaching and Learning in Action and International Perspectives and Initiatives .